Effects of Art on Surgical Patients: A Systematic Review and Meta-analysis. Issue 5 (November 2015) - Vetter, Diana; Barth, Jürgen; Uyulmaz, Sema; Uyulmaz, Semra; Vonlanthen, René; Belli, Giulio; Montorsi, Marco; Bismuth, Henri; Witt, Claudia M.; Clavien, Pierre-Alain
Abstract : Objectives: The aim of the study was to assess the effect of art including ambient features such as music, interior design including visual art, and architectural features on health outcomes in surgical patients. Background: Healing environments can have a positive influence on many patients, but data focusing on art in surgical patients remain scarce. Methods: We conducted a systematic search following the PRISMA guidelines from January 2000 to October 2014 on art in surgical patients. For music interventions, we pooled controlled studies measuring health outcomes (eg, pain, anxiety, blood pressure, and heart rate) in a meta-analysis. For other art forms (ambient and architectural features and interior design), we did a narrative review, also including nonsurgical patients, and looked for examples covering 3 countries. Results: Our search identified 1101 hits with 48 studies focusing on art in surgical patients: 47 studies on musical intervention and 1 on sunlight. The meta-analysis of these studies disclosed significant effects for music on pain after surgery, anxiety, systolic blood pressure, and heart rate, when compared with control groups without music. Effects of music were larger with self-selected music, and lower in surgical interventions performed under general anesthesia. Interior design features such as nature images and more spacious rooms, and architectural features providing more sunlight had positive effects on anxiety and postoperative pain. Conclusions: Self-selected music for surgical patients is an effective and low-cost intervention to enhance well being and possibly faster recovery. Although potentially very important, the impact of environmental features and spacious architecture with wide access to sunlight remains poorly explored in surgery. Further experimental research is needed to better assess the magnitude of the impact and cost effectiveness. Abstract : Supplemental Digital Content is available in the text